Peningkatan Daya Saing Usaha Ayam Geprek XYZ Menggunakan Metode Analisis SWOT - Septiono, Wakhid Lukas; Afrilia, Dwi; Marjohan, Masno (Universitas Pamulang, 2024)
MSME (Micro, Small, and Medium Enterprise)s are one of the businesses that are growing rapidly in society, which, without realizing it, has played a vital role in economic development and growth. Responding to these conditions, the government is making efforts to encourage the development of the digital economy and the digitalization of MSMEs. XYZ Geprek Chicken Business is one of the MSMEs that is also developing in this atmosphere. From the quantitative descriptive research that was conducted, it was shown that this business is in quadrant IV (Diversification) of the SWOT diagram, which means the business is in stable condition but facing serious challenges, so it is estimated that the business will experience difficulties if it only relies on existing strategies. Proposed diversification strategies that can be carried out by this business are: developing seasoning formulas; developing attractive promotions; collaborating with external parties; using technology; using halal, natural or BPOM-licensed ingredients; as well as menu differentiation.UMKM adalah salah satu usaha yang berkembang pesat di tengah masyarakat, yang tanpa disadari telah memainkan peran vital di dalam pembangunan dan pertumbuhan ekonomi. Menyikapi kondisi tersebut, pemerintah pun tengah melakukan upaya-upaya guna mendorong perkembangan ekonomi digital dan digitalisasi UMKM. Usaha Ayam Geprek XYZ merupakan salah satu UMKM yang turut berkembang di dalam atmosfer tersebut. Penelitan yang dilakukan secara kuantitatif deskriptif, menunjukkan bahwa usaha ini berada di kuadran IV (Diversifikasi) diagram SWOT, yang artinya usaha dalam kondisi mantap namun menghadapi tantangan berat sehingga diperkirakan roda usahanya akan mengalami kesulitan bila hanya bertumpu pada strategi yang ada. Usulan diversifikasi strategi yang dapat dilakukan oleh usaha ini yaitu: pengembangan formula bumbu; pengembangan promosi yang menarik; kerja sama dengan pihak eksternal; penggunaan teknologi; penggunaan bahan-bahan yang halal; alami maupun berlisensi BPOM; serta diferensiasi menu.